Persistent disparities in smoking among rural Appalachians: evidence from the Mountain Air Project - Kathryn Cardarelli; Susan Westneat; Madeline Dunfee; Beverly May; Nancy Schoenberg; Steven Browning (BMC, 2021)
Abstract Background Adult smoking prevalence in Central Appalachia is the highest in the United States, yet few epidemiologic studies describe the smoking behaviors of this population. Using a community-based approach, the Mountain Air Project (MAP) recruited the largest adult cohort from Central Appalachia, allowing us to examine prevalence and patterns of smoking behavior. Methods A cross-sectional epidemiologic study of 972 participants aged 21 years and older was undertaken 2015-2017, with a response rate of 82%. Prevalence ratios and 95% confidence intervals for current smoking (compared to nonsmokers) were computed for the entire cohort then stratified by multiple characteristics, including respiratory health. Adjusted prevalence ratios for current smoking versus not smoking were also computed. Results MAP participants reported current smoking prevalence (33%) more than double the national adult smoking prevalence. Current smoking among participants with a reported diagnosis of chronic obstructive pulmonary disease and emphysema was 51.5 and 53.3%, respectively. Compared to participants age 65 years and older, those age 45 years or younger reported double the prevalence of smoking (PR: 2.04, 95% CI: 1.51-2.74). Adjusted analyses identified younger age, lower education, unmet financial need, and depression to be significantly associated with current smoking. Conclusions Despite declining rates of smoking across the United States, smoking remains a persistent challenge in Central Appalachia, which continues to face marked disparities in education funding and tobacco control policies that have benefitted much of the rest of the nation. Compared with national data, our cohort demonstrated higher rates of smoking among younger populations and reported a greater intensity of cigarette use.